Problem Sharing Reflected In Elizabeth Noble's The Reading Group (2005): A Social Psychological Perspective - Nisa, Afifatun; M. Thoyibi, Drs., M.S., Dr. M. Thoyibi (2016)
This study is about Problem Sharing in Elizabeth Noble's novel The Reading Group (2005) analyzed using Social Psychological Perspective. The objectives of this study are to find what the problems are shared in the reading group, to describe the process of discussing the problem, and to analyze the reason of the author writing The Reading Group. This research is a qualitative research. The source of primary data in this research is Elizabeth Noble's The Reading Group novel (2005) published by New York: HarperCollins Publishers Inc. The sources of secondary data are from other sources related the study, such as website, dictionary, and some books that support the research. The researcher draws three conclusions in this research. Firstly, there are two types of problem shared in The Reading Group, namely: personal problem and group problem. Secondly, there are five ways to discuss the problem, such as direct, indirect, and pre-sharing while sharing, and post-sharing. Thirdly, Elizabeth Noble's reasons of writing The Reading Group, including sharing her own reading club experience, describing how women share experience one another, and the last is giving alternative to merely gossiping. Keywords: Problem Sharing, Reading Group, Women, Social Psychological.